2001
DOI: 10.1128/aac.45.2.589-592.2001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antianaerobic Activity of BMS 284756

Abstract: Anaerobes are becoming increasingly resistant to ␤-lactams due to ␤-lactamase production and other mechanisms. Although ␤-lactamase production, and concomitant resistance to ␤-lactams, is the norm among the Bacteroides fragilis group, other anaerobic gram-negative bacilli in the genera Prevotella, Porphyromonas, and Fusobacterium have increasingly become ␤-lactamase positive. ␤-Lactamase production also has been described for clostridia. Metronidazole resistance in organisms other than non-spore-forming gram-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
40
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 14 publications
3
40
0
Order By: Relevance
“…This is in accordance with previous but less extensive investigations. Hoellman et al (17) have reported a BMS-284756 (garenoxacin) MIC 50 of 0.5 g/ml and an MIC 90 of 2 g/ml for 357 recently isolated anaerobes of human origin. In a study by (29) reported MIC 50 s and MIC 90 s that were 2 to 4 log 2 dilutions lower than ours.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with previous but less extensive investigations. Hoellman et al (17) have reported a BMS-284756 (garenoxacin) MIC 50 of 0.5 g/ml and an MIC 90 of 2 g/ml for 357 recently isolated anaerobes of human origin. In a study by (29) reported MIC 50 s and MIC 90 s that were 2 to 4 log 2 dilutions lower than ours.…”
mentioning
confidence: 99%
“…It displays a high degree of in vitro activity against a broad range of gram-positive and gram-negative bacterial pathogens, including anaerobes (6,12,13,15,17,24,25,29,30).…”
mentioning
confidence: 99%
“…Preliminary data indicate that this drug has a broad spectrum of activity against most gram-positive and gram-negative aerobes and anaerobes, including certain strains that are resistant to other fluoroquinolones (3,8).…”
mentioning
confidence: 99%
“…Garenoxacin is a new des-F(6)quinolone that lacks the six-position fluorine characterizing the previous generation of fluoroquinolones. Preliminary data (4,8) indicate that this drug has a broad spectrum of activity against many grampositive and gram-negative aerobes and anaerobes, including certain strains that are resistant to other fluoroquinolones. Consequently, we studied the in vitro activity of garenoxacin against recent clinical isolates of G. vaginalis.…”
mentioning
confidence: 99%
“…While it is necessary to perform pharmacokinetic-pharmacodynamic studies before valid clinical conclusions may be drawn, garenoxacin's excellent activity against G. vaginalis, coupled with its activity against anaerobes (4,8), suggests that it deserves evaluation in the therapy of bacterial vaginosis and infections involving G. vaginalis. …”
mentioning
confidence: 99%